The house on Gryaznova Str in Irkutsk - Yanov, Yanov; Ryazanova, Olga (project baikal, 2026)
Vossoughian, N. (2020, June). Alvar Aalto, Ernst Neufert, and Architectural Standardization in Germany and Finland, 1933–45. The Journal of the Society of Architectural Historians, 79(2), 202-212. DOI:10.1525/jsah.2020.79.2.202